2004
DOI: 10.1016/j.jmarsys.2004.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Ecological stages of the Venice Lagoon analysed using landing time series data

Abstract: The time series of landings in the Venice Lagoon from 1945 to 2001 were analysed with the aim of explaining the ecosystem changes occurred. The comparative analysis of the total landings and mean Trophic Level (mTL) time series allowed to identify four different stages in the lagoon ecosystem. The first period, from 1945 to 1973, was characterised by increasing trends in the landings and their mTL. The second one, from 1974 to 1989, showed a decrease in the landings but still an increase in the mTL. The third … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 30 publications
(49 reference statements)
5
38
0
1
Order By: Relevance
“…A similar role has been identified for the introduced Manila clam Tapes philippinarum in the Venice Lagoon system (Pranovi et al, 2003). Furthermore, it was suggested that this strong top-down control of phytoplankton by T. philippinarum may be responsible for the system not returning to a phytoplankton-based trophic web (Libralato et al, 2004), although this seems unlikely in Independence Bay given the constant refreshment of productive waters that enter from outside the bay.…”
Section: Vulnerabilitiesmentioning
confidence: 99%
“…A similar role has been identified for the introduced Manila clam Tapes philippinarum in the Venice Lagoon system (Pranovi et al, 2003). Furthermore, it was suggested that this strong top-down control of phytoplankton by T. philippinarum may be responsible for the system not returning to a phytoplankton-based trophic web (Libralato et al, 2004), although this seems unlikely in Independence Bay given the constant refreshment of productive waters that enter from outside the bay.…”
Section: Vulnerabilitiesmentioning
confidence: 99%
“…The use of commercial fisheries has been widely employed as an indicator for ecosystem change (e.g. habitat modification and changes in primary productivity) (Libralato et al, 2004;Okada et al, 2005), and climate change (Qui et al, 2010). In particular, studies demonstrate a positive relationship between kelp and decapod abundances (Johns and Mann, 1987;Daly and Konar, 2010;Irigoyen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…During this period, the mean trophic efficiency of the lagoon was extremely low (i.e. 0.5%; Libralato et al 2004). Christian et al (2009) described a de crease in the mean trophic efficiency of the Neuse River estuary after a severe episode of hypoxia.…”
Section: Trophic Efficiencymentioning
confidence: 95%
“…Analysing the scientific literature on the topic, stress is usually associated with low system efficiency. For example, between 1974 and 1989, the Venetian Lagoon experienced a high level of eutrophication (Libralato et al 2004). During this period, the mean trophic efficiency of the lagoon was extremely low (i.e.…”
Section: Trophic Efficiencymentioning
confidence: 99%